2002
DOI: 10.1093/brain/awf234
|View full text |Cite
|
Sign up to set email alerts
|

Chronic, controlled GDNF infusion promotes structural and functional recovery in advanced parkinsonian monkeys

Abstract: The powerful trophic effects that glial cell line-derived neurotrophic factor (GDNF) exerts on midbrain dopamine neurones suggest its use in treating Parkinson's disease. However, some important questions remain about the possible therapeutic applications of GDNF. Here we demonstrate that the chronic infusion of 5 or 15 micro g/day GDNF into the lateral ventricle or the striatum, using programmable pumps, promotes restoration of the nigrostriatal dopaminergic system and significantly improves motor functions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
172
2
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 256 publications
(190 citation statements)
references
References 35 publications
11
172
2
2
Order By: Relevance
“…while intraventricular injections of GDNF were found to increase intrastriatal but not intranigral dopamine levels [43]. Infusion of GDNF into the putamen of MPTP-treated monkeys induced a gradual and significant reduction in parkinsonian symptoms [44]. This appeared to be a regenerative action, since GDNF was injected at three months after the MPTP lesion, when the nigrostriatal pathway had presumably undergone significant degeneration.…”
Section: Effects Of Gdnf In Vivomentioning
confidence: 99%
“…while intraventricular injections of GDNF were found to increase intrastriatal but not intranigral dopamine levels [43]. Infusion of GDNF into the putamen of MPTP-treated monkeys induced a gradual and significant reduction in parkinsonian symptoms [44]. This appeared to be a regenerative action, since GDNF was injected at three months after the MPTP lesion, when the nigrostriatal pathway had presumably undergone significant degeneration.…”
Section: Effects Of Gdnf In Vivomentioning
confidence: 99%
“…[37][38][39] Unlike the case with BDNF, however, there is also evidence for restoration of function of injured neurons by GDNF after toxic insults 33,36,40 although restorative actions are generally not as dramatic as the neuroprotective actions. 33 A series of influential studies from Gash, Gerhardt, and coworkers [41][42][43] have demonstrated GDNF-induced improvement in bradykinesia, rigidity, and postural instability in monkeys with stable MPTP-induced hemiparkinsonism. GDNF was effective when given by bolus or by constant infusion, and through three routes of administration: intranigral, intrastriatal, and intracerebroventricular (ICV).…”
Section: Gdnfmentioning
confidence: 99%
“…Procedures were described previously (3,7). For the nigral DA levels in the animals with pallidal lesins, 10 tissue punches from the right SN (ipsilateral to the MPTP administration and the pallidal lesion) from each monkey were obtained from the 4 mm thick coronal section throught the SN as previous described (14).…”
Section: Histology and Neurochemistrymentioning
confidence: 99%
“…Studies from our group have consistently demonstrated that intracerebral administration of GDNF could not only significantly improve overall parkinsonian features, but also increase levels of dopamine (DA) and homovanillic acid (HVA), a metabolite of dopamine, especially in the pallidal regions in which the changes of DA and HVA in the GP were even more robust than what were observed in the caudate and putamen in normal (3), aged (4) and parkinsonian monkeys (5,6,7). For example, in the aged animals (4), robust increases of DA were found in the globus pallidus by 390% (P<0.01) on the GDNF-treated hemisphere compared with 50% (P<0.05) in the caudate nucleus, while the increase of DA failed to reach significance in the putamen following GDNF administration.…”
Section: Introductionmentioning
confidence: 95%